2021
DOI: 10.1186/s12882-021-02303-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal attitudes of control and responsibility for the uptake of peritoneal dialysis- a national survey among dialysis patients

Abstract: Background Although most patients are suitable for both hemodialysis (HD) and peritoneal dialysis (PD), there seem to be differences in the outlook of patients who choose one modality over the other. There is currently limited literature about the impact of patients’ personal attitudes on the decision for PD or HD. In this study, we tried to find out whether there were differences between patients who were on HD and PD in their desire for control and responsibility for their treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The question that arises is why PD patients have such a low rate of vaccine hesitancy than HD counterparts? Likely a better understanding of own health status and a high level of accountability in PD patients may explain a higher rate of COVID-19 vaccine acceptance in this population [ 20 ]. Another hypothesis may be the exclusion of vulnerable and marginalized patients from PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The question that arises is why PD patients have such a low rate of vaccine hesitancy than HD counterparts? Likely a better understanding of own health status and a high level of accountability in PD patients may explain a higher rate of COVID-19 vaccine acceptance in this population [ 20 ]. Another hypothesis may be the exclusion of vulnerable and marginalized patients from PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, patients undergoing PD are perhaps more likely-implicit to their eligibility and subsequent selection of this home-based modality-to have better functional status, prioritize autonomy and self-directed care, a higher degree of psychosocial support, or both. [13] As a result, the need for kidney supportive care in PD patients may be even greater than that of those on HD due to 1) potentially greater decision-making complexity and wider range of treatment options to consider; 2) greater magnitude of prognostic uncertainty with fewer available prognostic tools, 3) possible differences in range or type of symptoms experienced; and 4) subsequent importance of understanding individual PD patient motivations. These issues necessitate attention to upstream, longitudinal goal-directed conversations that adapt with PD patients' values and priorities over time.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In a large survey in Germany of over 600 maintenance patients, investigators showed that patient attitudes regarding dialysis may differ between patients electing PD versus HD; PD patients prioritized autonomy and/or taking control of their own care in dialysis modality selection. [59] Coping strategies most often utilized by PD patients in the Empowering Patients on Choices for Renal Replacement Therapy (EPOCH-RRT) cohort were cognitive restructuring and problem solving; although social support was also identified as a coping strategy for some, it was not as frequently employed as by HD patients. [60] These results provide insight into some of the most prominent patient-described perspectives and motivations of PD patients.…”
Section: What Are Pd Patient Priorities?mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals choosing PD show high desire for control and are confident in taking responsibility for their therapy. 42 Patient/caregiver perceived advantages and drawbacks of APD are summarized in Table 2.…”
Section: Patient's Values and Perceived Outcomesmentioning
confidence: 99%